2016
DOI: 10.18632/oncotarget.9311
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-126-3p suppresses cell proliferation by targeting PIK3R2 in Kaposi's sarcoma cells

Abstract: Kaposi's sarcoma is a highly vascular tumor of lymphatic endothelial origin. Many deregulated miRNAs, including miR-126-3p, have been identified in Kaposi's sarcoma tissues. miR-126-3p is the most highly endothelial-specific miRNA that regulates vascular integrity and angiogenesis. In this study, we aimed to determine the effect of miR-126-3p on Kaposi's sarcoma cells through transfection of a miRNA mimic and inhibitor. Moreover, we searched the target gene (PIK3R2) of miR-126-3p using bioinformatics software … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…Pathway analysis showed that cell adhesion molecules were significantly regulated by both miR-126-3p and miR-126-5p. MiR-126-3p transfection significantly decreased PIK3R2 mRNA levels, which is a known target of miR-126-3p [22] (Table 1). MiR-126-5p similarly significantly decreased its targets high-mobility group protein (HMGB)1 and vascular endothelial growth factor (VEGF)α (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Pathway analysis showed that cell adhesion molecules were significantly regulated by both miR-126-3p and miR-126-5p. MiR-126-3p transfection significantly decreased PIK3R2 mRNA levels, which is a known target of miR-126-3p [22] (Table 1). MiR-126-5p similarly significantly decreased its targets high-mobility group protein (HMGB)1 and vascular endothelial growth factor (VEGF)α (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…To assess whether miR-126-3p was able to regulate these putative target genes, we transfected the T-cell leukemia cell line Jurkat with a miR-126-3p mimic and we evaluated the impact of its ectopic expression on AKT2 , PPP3CB , RANKL, and SDC2 transcript levels. We used PIK3R2 as positive control of the miRNA mimic, since it is a well-known miR-126-3p target [ 30 ]. After 48 hours from transfection, miR-126-transfected cells expressed significantly lower levels of all the targets as compared to the mimic control ( Figure 5(d) ).…”
Section: Resultsmentioning
confidence: 99%
“…Chen et al ( 46 ) demonstrated that miR-126-3p was associated with advanced pathological stage and lymph node metastasis in patients with lung adenocarcinoma. miR-126-3p is the most endothelial-specific miRNA that alters vascular integrity and angiogenesis, and it served as a tumor inhibitor targeting phophoinositide-3-kinase regulatory subunit 2 in Kaposi's sarcoma cells ( 47 ). Its expression appeared to be upregulated in colon cancer, as demonstrated by Ji et al ( 48 ).…”
Section: Discussionmentioning
confidence: 99%